PENINGKATAN KESADARAN LINGKUNGAN MELALUI PROGRAM PENGENALAN DAN PENANAMAN TANAMAN OBAT KELUARGA - Khotijah, Siti (ABDISUCI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
In this modern era, awareness of the importance of environmental conservation and sustainable use of natural resources is increasingly urgent. To increase environmental awareness and public health through the introduction and planting of family medicinal plants (TOGA) program. This program was carried out in Campaka Village which involved active community participation in educational activities and TOGA planting practices. In a global context that is increasingly concerned about environmental damage and declining health quality, TOGA is an effective and sustainable solution.The research results show that this program has succeeded in increasing people's knowledge about the benefits of medicinal plants, as well as changing their mindset regarding the importance of maintaining biodiversity. Apart from that, people also feel the direct benefits of TOGA in their family's health. These findings indicate that the introduction and planting of TOGA can be an effective strategy for increasing environmental awareness and supporting the sustainability of local ecosystems.